The Design Equation for Gains of Non-ideal Proportional-Resonant Controller used in Control of Single-Phase Grid-Connected Inverter - พันธุ์ออน เจษฎา; แสงธงทอง วิโรจน์ (Srinakharinwirot University Engineering Journal, 2020)
This paper provides the design equation evaluating the gains of non-ideal proportional plus resonant controller also known as non-ideal PR controller. The control system of single-phase grid-tied inverter typically embraces such a PR controller governing grid-current. The design equation is originated and developed from the characteristic equation of the closed-loop control system. Either two distinct negative real closed-loop poles or one complex-conjugate pair of closed-loop poles with negative real part are required for the PR gain computations of the design equation. Root-locus consideration will place the two distinct negative real poles whilst specification of transient response will assign the one complex-conjugate pair of poles. The PR controller has to carry its gains so that the closed-loop system becomes stable. Simulation results compare transient responses of grid current derived from entering two different couples of closed-loop poles into the design equation and then allowing it to run. Grid-current response tracking its reference and synchronization between grid current and grid voltage in steady state are accomplished under experiments on the control system. Thus, the proposed design equation is an alternative way for tuning the gains of the PR controller in practice.